The effect of carbon pricing on technological change for full energy decarbonization: A review of empirical ex‐post evidence. (30th September 2020) - Lilliestam, Johan; Patt, Anthony; Bersalli, Germán
Abstract: In order to achieve the temperature goals of the Paris Agreement, the world must reach net‐zero carbon emissions around mid‐century, which calls for an entirely new energy system. Carbon pricing, in the shape of taxes or emissions trading schemes, is often seen as the main, or only, necessary climate policy instrument, based on theoretical expectations that this would promote innovation and diffusion of the new technologies necessary for full decarbonization. Here, we review the empirical knowledge available in academic ex‐post analyses of the effectiveness of existing, comparatively high‐price carbon pricing schemes in the European Union, New Zealand, British Columbia, and the Nordic countries. Some articles find short‐term operational effects, especially fuel switching in existing assets, but no article finds mentionable effects on technological change. Critically, all articles examining the effects on zero‐carbon investment found that existing carbon pricing scheme have had no effect at all. We conclude that the effectiveness of carbon pricing in stimulating innovation and zero‐carbon investment remains a theoretical argument. So far, there is no empirical evidence of its effectiveness in promoting the technological change necessary for full decarbonization. This article is categorized under: Climate Economics > Economics of Mitigation Abstract : Our review of empirical ex‐post evaluations of the effects of existing carbon pricing schemes reveals some effects on operational shifts, mainly switching coal to gas power, but no effect on the technological change necessary for full decarbonization.